Desain E-Magazine Pada Mata Pelajaran Biologi Bermuatan High Order Thingking Skill (HOTS) Untuk Siswa SMA/MA - Nining Nuraida; Try Susanti; M. Syahran Jailani (Jurnal Biotek, 2022)
This study aimed to design an e-magazine containing High Order Thinking Skills (HOTS) for SMA or MA students. This development followed the ADDIE process: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The product underwent alpha testing with the help of two media experts and two material experts. Small-scale product beta testing involved ten students from class XII, with a field trial involving 22 students from class XI SMA. Interviews, observations, and questionnaires were used to collect the data. The data was analyzed using qualitative descriptions. The results of product testing at the alpha test showed that e-magazines designed by media experts have an average score of 3.55 in the very positive category. For material experts, the score was 3.36, which was very good. The results of the small-scale beta test gave an average rating of 3.56, which means this e-magazine has a very decent design. The field test has an average value of 3.6, a very positive category. The results of the student effectiveness test showed an average score of 48 for the pre-media test and 80.73 for the post-media test. The N-gain score obtained was 0.629 with the moderate criteria. It seems that this media proved to be feasible and effective in learning for XI SMA or MA students.